Origin of myeloid cells - Geissmann, Frederick A. (Henry Stewart Talks, 2012)
Definition of monocytes, macrophages and dendritic cells, Role of these cells in controlling innate inflammatory response and memory immune responses, Involvement of the innate immune system in the pathophysiology of infectious and inflammatory diseases, Development of different types of immune cells from different precursors, The transcription factors and growth factors required to differentiate precursor cells into specific immune cells